Sinalização endógena do sistema Nociceptina/Orfanina FQ - receptor NOP: envolvimento na modulação da depressão experimental induzida por lipopolissacarídeo - Medeiros, Iris Ucella de (2015)
During the last decades, it has been established that there is a relationship between major depression and activation of immune system. Nociceptin/orphanin FQ (N/OFQ) is the natural ligand of a Gi-protein coupled receptor named NOP, both compose the peptidergic system wich is involved in the regulation of mood states and inflammatory responses. Considering these actions, the present thesis aimed to investigate the consequences of blocking NOP signaling in lipopolysaccharide (LPS)-induced sickness and depressive-like behaviors in mice. Systemic administration of LPS doses, that do not cause sepsis in mice, induce changes in their behaviors related with activity of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukins 6 (IL-6) and 1β (IL-1 β). At the time points of 2 to 6 h and 24 h after intraperitoneal injection, mice treated with LPS displayed, respectively, sickness and depressive-like behaviors. In the present work the administration of LPS 0.8 mg/kg (ip) significantly induced sickness signs in Swiss and CD-1 mice, such as weight loss, transient reduction in rectal temperature and decrease of food and water intake. Moreover at 24 h after LPS injection these same mice strains displayed significantly increased immobility time on the tail suspension test (TST) when compared with control mice, this alteration was not related with possible locomotion impairments as verified on the open field test. Treatment with Nortriptyline 30 mg/kg (ip, 60 min prior the TST) reduced the immobility time of control and LPS-treated mice and was used as standard antidepressant. The NOP receptor antagonist SB-612111 (10 mg/kg, ip), 30 min prior LPS, did not modify LPS-induced sickness signs and depressive-like behavior. However, when injected 24 h after LPS treatment, SB-612111 (ip, 30 min prior the TST) as well as the peptidergic NOP receptor antagonist UFP-101 (10 nmol/2μL, icv, 5 min prior the TST) significantly reversed the toxin effects. The protocol of LPS-induced depressive-like states was also tested in NOP receptor knockout mice (NOP(-/-)) and their respective wild types (NOP(+/+)). LPS evoked transient rectal temperature reduction in NOP(-/-) mice and loss of body weight, food and water intake reduction in both NOP(+/+) and NOP(-/-) mice. The consumption of water was significantly different due to the genotype. LPS injection induced transient changes in pro-inflammatory cytokines. At 6 h after LPS injection, serum levels of TNF-α were significantly increased in NOP(+/+) and NOP(-/-) mice, as the IL-6 levels were significantly increased just in NOP(+/+) serum. At 24 h after LPS treatment the pro-inflammatory cytokines had returned to the baseline levels in both genotypes. LPS treatment elicited depressive-like effects in NOP(+/+) but not in NOP(-/-) mice. The data obtained during the execution of this doctoral thesis reveal that pharmacological and genetic blockade of NOP signaling does not affect LPS evoked sickness signs while reversing depressive-like behavior. In conclusion, these results highlight the involvement of the peptidergic system N/OFQ - NOP receptor in the modulation of behaviors related to mood and activation of the immune system.